Medical quiz human anatomy - Tin, Tin Myint (Penerbit Universiti Malaysia Sabah, 2011)
A medical quiz book is the best mode of student-centred learning method. Since most textbook in anatomy are vivid with minute details which are difficult to memeorise and retrieve, this book could be a great help for students to remember those details.